Capacitive Properties of Chlorine Doped Graphene Quantum Dots Anchored into Reduced Graphene Oxide. (1st July 2022) - Lei, Yun; Li, Can; Du, Peng; Wu, Yuncui; Luo, Linhui; Wang, Yongqin; Du, Beibei; Wang, Shiquan
Abstract : In this study, Cl-GQDs anchored into pure reduced graphene oxide (Cl-GQDs/rGO) hybrid materials were hydrothermally fabricated and characterized by various analyses. Meanwhile, P-GQDs, S-GQDs and N-GQDs were also fabricated and anchored into rGO as controls. The AFM images of Cl-GQDs, P-GQDs, N-GQDs and S-GQDs displayed the average height of 1–3 nm, 1–1.5 nm, 1.5–2.0 nm and 4.0–4.5 nm, respectively. Moreover, the absorbance and fluorescence spectra of Cl-GQDs were different from those of other doped graphene quantum dots. Cyclic voltammetry and galvanostatic charge-discharge curves were employed to analyze the capacitive performances of doped-GQDs/rGO. At the current density of 2 A g −1, the capacitance of Cl-GQDs/rGO achieved 316 F g −1, which was about 3 times, 2 times and 1.5 times as high as that of rGO, S or N-GQDs/rGO and P-GQDs/rGO, respectively. At the power density of 1.1−3.3 KW Kg −1, Cl-GQDs/rGO reached the energy density of 53.2 − 32.1 Wh Kg −1 . Electrochemical impedance spectroscopy clearly indicated that Cl-GQDs could improve the conductivity of rGO in the electrochemical reaction, resulting in superior capacitive performances.